2010
DOI: 10.1007/s11060-010-0319-1
|View full text |Cite
|
Sign up to set email alerts
|

Growth curve analysis of asymptomatic and symptomatic meningiomas

Abstract: Meningiomas sometimes appear to stop growing after attaining a large size. Commonly used exponential growth models do not reflect this phenomenon. We attempted to find the best curve to simulate their growth. Fifty-two patients with meningioma were followed up for 3.1-21.7 years (mean 7.5 years) with four or more imaging studies each. Thirty-one patients had asymptomatic tumors. The other 21 patients with residual or recurrent tumor were followed up after surgery. Time-volume curves for each tumor were plotted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 28 publications
2
66
3
Order By: Relevance
“…Nine of them could be statistically evaluated in our meta analysis [4,5,7,9,11,13,16,17,21], calcification was associated with significantly reduced risk of growth (P= 0.001). Furthermore Nakusa etal and Jadid etal [8,12] concluded the same results with different way of calculation. Only Hashiba et al reported that the presence of calcifications was more frequently observed in lesions that followed a linear growth pattern than in those following an exponential pattern (P= 0.05) [5] .…”
Section: Mri Findingsmentioning
confidence: 64%
See 2 more Smart Citations
“…Nine of them could be statistically evaluated in our meta analysis [4,5,7,9,11,13,16,17,21], calcification was associated with significantly reduced risk of growth (P= 0.001). Furthermore Nakusa etal and Jadid etal [8,12] concluded the same results with different way of calculation. Only Hashiba et al reported that the presence of calcifications was more frequently observed in lesions that followed a linear growth pattern than in those following an exponential pattern (P= 0.05) [5] .…”
Section: Mri Findingsmentioning
confidence: 64%
“…Studies by Yoneoka et al , Herscovici et al ,Oya etal and Nakusa etal found patients with growing tumors were younger than those with non-growing tumors. Regarding growth curve analysis Nakusa reported that majority of benign meningiomas began to slow their growth before age of 80 years [12]. From our meta-analysis, we found that the overall effect suggests that growth was more likely in young age patients (P<0.001).…”
Section: General Demographicsmentioning
confidence: 67%
See 1 more Smart Citation
“…3 Only 3%-6% of clinically detected asymptomatic meningiomas later become symptomatic. 5 When symptomatic, intracranial meningiomas present a wide variety of symptoms arising from the compression of adjacent structures, direct invasion of or reactive changes in the adjacent brain tissue, and obstruction of cerebrospinal fluid pathways, cortical veins, or major venous sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…2 Meningiomas are benign, slow growing tumours with a long initial asymptomatic phase. 3 The neurological deficit seemed to be related to the tumour location and size, and the severity of the peritumoural oedema. The considerable peritumoural oedema, probably related to their cellular morphology and ability to release vasoactive substances.…”
Section: Introductionmentioning
confidence: 96%